Recent Advances in Transition Metal Nitride‐Based Materials for Photocatalytic Applications - Cheng, Zhixing; Qi, Weiliang; Pang, Cheng Heng; Thomas, Tiju; Wu, Tao; Liu, Siqi; Yang, Minghui (Advanced functional materials, 2021)
Photocatalysis is a promising and convenient strategy to convert solar energy into chemical energy for various fields. However, photocatalysis still suffers from low solar energy conversion efficiency. Developing state of the art photocatalysts with high efficiency and low cost is a huge challenge. Transition metal nitrides (TMNs) as a class of metallic interstitial compounds have attracted significant attention in photocatalytic applications. In fact, TMNs exhibit multifunctional properties in various photocatalytic systems. This review is the first attempt that summarizes recent research on TMNs‐based materials in various photocatalytic applications. Different roles of TMNs materials in photocatalytic systems including semiconductor active components, co‐catalysts, inter‐band excitation, and surface plasmon resonance components are systematically discussed and summarized. The fundamentals, latest progress, and emerging opportunities for further improving the performances of TMNs‐based materials for photocatalysis are also discussed. Finally, some challenges facing TMNs, and perspectives on their future that are relevant for furthering research in the area of photocatalysis are also proposed. This review summarizes recent research on TMNs‐based materials in various photocatalytic applications including water splitting, CO2 reduction, and dye degradation. Different roles of TMNs materials in photocatalytic systems such as semiconductor active components, co‐catalysts, inter‐band excitation, and surface plasmon resonance components are systematically discussed and summarized.